Unfrozen state by the supercooling of chuño for traditional agriculture in altiplano andes - Yoshikawa, Kenji (2020)
The freezing point and supercooling process are discussed for their impact on the traditional Andean freeze-dried potatoes called chuño. The freezing point depends on potato species, but typically it is slightly below zero to −3 ​°C; supercooling always occurs before the potatoes freeze, and the lowest supercooling point (LSP) can reach −4.3 ​°C. Recently many of the potato fields near Lake Titicaca are not cold enough to freeze tubers for chuño, and the loss of this food source will be critical in the future.